2017
DOI: 10.4314/ijbcs.v10i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Composition and dynamic of benthic macroinvertebrates community in semi-arid area rivers of Burkina Faso (West Africa)

Abstract: The benthic macroinvertebrates communities dynamic were investigated in rivers from Burkina Faso in the purpose to analyze the taxonomic composition, the structure of benthic macroinvertebrates community and the composite environmental variables that correspond to the major distribution patterns of this community. The results showed that a total of 132 taxa was recorded and the large majority of these (103 taxa) belonged to 57 families from 8 orders of insects that represent 95% of relative abundance. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Koga Dam construction has been completed in 2010 [ 26 ] and the littoral zones of the reservoirs had low vegetation cover. Vegetation provides shelter and various resources for prey and restricts the efficiency of predation, thereby enhancing biotic diversity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Koga Dam construction has been completed in 2010 [ 26 ] and the littoral zones of the reservoirs had low vegetation cover. Vegetation provides shelter and various resources for prey and restricts the efficiency of predation, thereby enhancing biotic diversity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To provide cost-effective tool accessible locally for ecological assessments, there is an increasing emphasis on the use of BIs [25,26]. BIs based on macroinvertebrates are developed or applied in many countries including some developing countries such as South Africa, whereas in West Africa, there is a deficiency of information on the use of macroinvertebrates and biotic indices for water quality and ecosystem health assessment [27][28][29][30][31][32][33].…”
Section: Biotic Indices (Bis)mentioning
confidence: 99%
“…Effects of those anthropic multiples pressures on water ecosystems are rendering benthic macroinvertebrate assemblages among others aquatic organisms more vulnerable including change of community composition, increase of opportunistic species number, and decline of sensitive taxa and general biodiversity. In West Africa, several authors such as Tampo et al [28], Kaboré et al [29], Kaboré et al [30], Tampo et al [31], Agblonon Houelome et al [32], and Edegbene et al [33] among others have demonstrated the sensitivity of macroinvertebrates to water quality and human disturbances. From these authors, the macroinvertebrates community including functional surrogates, taxonomic composition, and diversity reflect the environmental condition, and any modification from physical, chemical, and biological integrity of freshwater ecosystems can dramatically affect water and biological resources, and as human health.…”
Section: Promising Tools Using Macroinvertebrates For Ecosystem Healt...mentioning
confidence: 99%
“…Macroinvertebrates are composed of Arthropods, Annelids and Molluscs, are often amongst the first animals to colonize artificial lakes to reproduce. Many studies have shown that the majority of macroinvertebrates in natural aquatic ecosystems are one of the most diverse groups [1], [2], [3] and [4]. However, the studies on the benthic fauna in artificial lakes in Sahel region remains fragmentary, despite their important role in maintaining the balance of biota in aquatic ecosystems [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these artificial waterbodies are also populated by several species of fish, amphibians and aquatic birds. Many studies have shown that aquatic biota, and particularly the macroinvertebrates are key animals in water because they are mostly influenced by several factors such as ecosystem types, waters variables and multiple anthropogenic pressures [4], [6], [7], [8], [9], [10] and [11]. These men-made lakes provide several advantages but they rarely documented.…”
Section: Introductionmentioning
confidence: 99%